The use of an analog sclerometer to estimate strength of hard substrates supporting coastal communities - Alli N. Cramer; Curt D. Storlazzi; Olivia Bible; Cannon Cline; Grace Leuchtenberger; Casey Smith; Corey Garza; Emily Carrington (Estuarine, Coastal and Shelf Science, 2026)

In Pursuit of Conference Equity - Isabel Martínez-Farrington; Loraine Bonet; Aixa Alemán-Díaz; Justin Ballenger; Dwight Ebanks; Mona Behl; Sarah Kolesar; Sharon Cooper; Corey Garza; Jonathan Lewis; Brandon Jones; Lisa White (Oceanography, 2024)
Scientific meetings and conferences are a cornerstone of scientific culture. By bringing people together around a shared purpose, meetings serve as a platform for knowledge exchange and can often foster a sense of belonging. As some will argue, conferences can become “counterspaces” to affirm a person’s identity, provided they have adequate access to resources and support (Nakajima et al., 2024). From students to retirees, scientific meetings and conferences provide engagement and professional development opportunities for people from various career tracks and stages and serve as engines of innovation and collaboration. As a major source of revenue, meetings and conferences are also integral to the business models of many professional societies, publishers, exhibitors, businesses, and local economies.

Re-Envisioning Undergraduate Research Experiences to Increase Diversity, Equity, and Inclusion, and Harness the Power of Diversity in Ocean Sciences - Paul Barber; Catalina Martinez; Corey Garza; Deidre Gibson; Alexandra Davis (Oceanography, 2023)
Diversity in ocean sciences lags far behind US demographics. A substantial body of research highlights barriers that limit the participation and success of students from underrepresented minoritized (URM) and other marginalized groups in STEM disciplines, and a wealth of studies highlight successful interventions that improve the persistence of these groups in STEM higher education. Despite this knowledge, over the past four decades, ocean sciences has made limited progress in growing diversity within its workforce, suggesting new strategies are needed. Undergraduate research experiences are a pivotal pathway toward graduate education and future careers in ocean sciences, but they are plagued by many issues that limit the participation and success of persons from URM and other marginalized backgrounds. Here we summarize obstacles that limit participation of diverse populations in ocean sciences and highlight successful strategies for overcoming these obstacles. By re-envisioning how we approach undergraduate research experiences and bringing intentionality to the recruitment of students and the training environments that they experience, we can more effectively grow diversity in ocean sciences and unleash the power of diversity to address the pressing local and global problems facing marine ecosystems.

Introduction to the Special Issue on Building Diversity, Equity, and Inclusion in the Ocean Sciences - Ellen Kappel; Benjamin Cuker; Corey Garza; Deidre Gibson; Catalina Martinez; Wendy Todd; Cassie Xu (Oceanography, 2023)
In his inaugural “The Oceanography Classroom” column for Oceanography in 2000, Dean McManus noted: “A particular challenge for higher education is to include more members of underrepresented groups in the study of the ocean. Fifteen years from now, 40% of the traditional undergraduate-​​age population will consist of these underrepresented groups, but today the ocean sciences have the lowest participation by underrepresented groups of any science” (McManus, 2000). Why should we care about this lack of diversity in the ocean sciences? As a recent US National Science Foundation report puts it, “A diverse workforce provides the potential for innovation by leveraging different backgrounds, experiences, and points of view. Innovation and creativity, along with technical skills relying on expertise in science, technology, engineering, and mathematics (STEM), contribute to a robust STEM enterprise” (NSF, 2023a). To put it more succinctly, “diversity is not distinct from enhancing overall quality—it is integral to achieving it” (Gibbs, 2014). Having a diverse, inclusive, and equitable workforce is not only a valuable objective and moral imperative, it is essential for fulfilling future workforce needs.

Changing the Culture of Coastal, Ocean, and Marine Sciences: Strategies for Individual and Collective Actions - Mona Behl; Sharon Cooper; Corey Garza; Sarah Kolesar; Sonya Legg; Jonathan Lewis; Lisa White; Brandon Jones (Oceanography, 2021)
Geoscience is plagued with structural and systemic barriers that prevent people of historically excluded groups from fully participating in, contributing to, and accruing the benefits of geosciences. A change in the culture of our learning and working environments is required to dismantle barriers and promote belonging, accessibility, justice, equity, diversity, and inclusion in our field. Inspired by a session organized at the 2020 Ocean Sciences Meeting, the goal of this paper is to provide a consolidated summary of a few innovative and broadening participation initiatives that are being led by various stakeholders in academia (e.g., students, faculty, administrative leaders) at different institutional levels (e.g., universities, professional societies). The authors hope that the strategies outlined in this paper will inspire the coastal, ocean, and marine science community to take individual and collective actions that lead to a positive culture change.

Diversifying the Ocean Sciences: Thoughts on the Challenge Ahead - Corey Garza (Oceanography, 2021)
The lack of diversity in the ocean sciences is not a particularly big secret or a recent issue. In his inaugural column in 2000 for The Oceanography Classroom, Dean McManus wrote: “A particular challenge for higher education is to include more members of underrepresented groups in the study of the ocean. Fifteen years from now, 40% of the traditional undergraduate-age population will consist of these underrepresented groups, but today the ocean sciences have the lowest participation by underrepresented groups of any science.” Despite this prescient statement from McManus, little progress has been made in diversifying the ranks of the ocean sciences. In a recent National Science Foundation survey of current graduate students in the ocean sciences, approximately 8.8% of those surveyed identify as coming from a group that is considered part of a minority community in the United States (Black, Hispanic/Latinx, Native Alaskan, Native American, Pacific Islander). As might be expected, these numbers are even worse for the professional ranks of agencies, nonprofits, and university programs that focus on the ocean sciences. The lack of these communities’ representation in ocean science careers is underscored by the past year’s news reports, brimming as they have been with the brutality and injustices that those in BIPOC (Black, Indigenous, People of Color) communities face daily. The STEM community, including the ocean sciences, is now, more than ever, being forced to confront the ways in which its institutions and culture contribute to the inequities facing BIPOC communities. Here, I draw upon my dual identity as a member of the ocean science and Latinx communities to discuss how the ocean sciences can enact meaningful changes around improving diversity, equity, and inclusion (DEI).

Landscape Ecology in the Rocky Intertidal: Opportunities for Advancing Discovery and Innovation in Intertidal Research - Corey Garza (Current Landscape Ecology Reports, 2019)

Lingcod (Ophiodon elongatus) habitat associations in California: implications for conservation and management - Megan Bassett; James Lindholm; Corey Garza; Rikk Kvitek; Deb Wilson-Vandenberg (Environmental Biology of Fishes, 2018)

Landscape Complexity Effects on Fisheries: Insights from Marine Landscape Ecology - Corey Garza (Current Landscape Ecology Reports, 2016)

Effects of brackish water incursions and diel phasing of tides on vertical excursions of the keystone predator Pisaster ochraceus - Corey Garza; Carlos Robles (Marine Biology, 2010)

Complex equilibria in the maintenance of boundaries: experiments with mussel beds - Carlos D. Robles; Robert A. Desharnais; Corey Garza; Megan J. Donahue; Carlos A. Martinez (Ecology, 2009)
Stationary boundaries of sedentary species may belie dynamic processes that form them. Our aim was to test an implication of an evolving body of theory, that such boundaries are manifestations of complex regulatory dynamics. On rocky shores of British Columbia, large‐scale field experiments altered the densities of predatory sea stars ( Pisaster ochraceus ), causing shifts in the location of the lower vertical boundaries of their prey, sea mussels ( Mytilus californianus ). While control mussel beds remained unchanged, experimental reductions of sea star densities caused the downward extension of the lower boundaries, and experimental increases in sea stars densities caused the upward recession of the lower boundary well into the zone presumed to be a spatial refuge from predation. Cleared plots prepared within the initial boundaries were recolonized to varying degrees, depending on predator densities. After 30 months, plots on sea star removal sites showed high densities of adult mussels, control plots showed intermediate densities, and sea star addition plots showed only a sparse cover of alternative prey. Observations by divers at high tide showed that as small prey were depleted progressively from removal, to control, to addition sites, correspondingly larger mussels were attacked, including very large individuals comprising the lower boundary of addition sites. The findings contradict classic theory of zonation based on static prey refuges and support an alternative theory in which boundaries are maintained by complex, spatially structured equilibria.